Malocclusion and speech therapy and associated factors: integrative review (Research, Society and Development, 2021)
Malocclusion can be defined as the abnormal alignment of teeth or a poor relationship between dental arches so that the upper and lower teeth fit together, thus causing structural and functional changes. To evaluate the profile of malocclusion and associated factors of individuals undergoing speech therapy through a literature review. For conducting the research, the method of integrative review was chosen, with a qualitative approach, a bibliographic survey was carried out by consulting the databases: Lilacs, Scielo and Pubmed. The descriptors used in the research were Epidemiology, Orthodontics, and Speech Therapy. As an inclusion criterion, complete scientific articles were established only in Portuguese and English, in the years 2015 to 2020. After selecting the study abstracts found, five were included in the study. After searching the databases, one hundred and fifty articles were found, Pubmed 70, Lilacs 41, Scello 44, after studies of titles and abstracts inconsistent with the theme, 114 and 26 were excluded due to duplication, were selected for eligibility 20, after full reading of the sample consisted of five scientific articles, selected by the inclusion criteria previously established. After analyzing the articles selected for this review, in order to facilitate reading and understanding, the results were grouped into categories: level of evidence, classification of occlusion and associated factors. It is concluded that the interdisciplinary work between dentistry and speech therapy is relevant for the aesthetic and functional restoration.